Hot-bath epilepsy. - Pall, H. S. (BMJ Group, 1987)
Immersion in hot baths is an infrequently recognized cause of reflex epilepsy. Two such cases are described. Increased awareness of unusual forms of reflex epilepsy is necessary as this may have important prognostic and therapeutic implications.